Vibration analysis of screw-fed systems used in additive manufacturing technology - ERSOY, SEZGİN (My University, 2022)
Additive manufacturing technology has become quite widespread and produces solutions in many areas. Although it is much more advantageous than machining, this technology continues to be developed every day to increase productivity. In additive production systems with different production processes, it may be necessary to improve the system in order to increase the quality of the products that are desired to increase the sensitivity. In this study, it is aimed to determine the vibration behavior of the screw used in the screw extruder method, which will eliminate the errors caused by the continuous filament technology used in FDM technology in layered production. Keywords: additive manufacturing, screw extrusion, vibration analysis.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); additive manufacturing; screw extrusion; vibration analysis.